CRANIAL CRUCIATE LIGAMENT RUPTURE IN THE DOG AND ITS RESOLUTION USING THE SURGICAL TECHNIQUE TPLO - : CASE REPORT - Alcantara Garcia, Giovana; Gomes Vespoli, Lucas (Journal of Interdisciplinary Debates, 2021)
It is known that the cranial cruciate legament is one of the main stabilizers of the knee, and problems in it can bring complications to the animal, including the rupture of the cranial cruciate ligament, which is classified as one of the biggest diseases in the pelvic limbs in dogs. Its diagnosis is made through a thorough consultation and, during the physical exam, the drawer and tibial compression tests. However, as a confirmatory diagnosis, complementary imaging exams are used for a better visualization of suspicious problems. Conservative and surgical treatments are included in its treatment, where the surgical ones include extracapsular, intracapsular, and corrective osteotomies, the latter being the most modern and safest in terms of possible relapse and future joint degeneration, because they are procedures that modify the bone anatomy, restoring stability and returning function to the limb; however, the choice of treatment is always made individually for each patient. Thus, the present study aims to report the case of a patient with rupture of the cranial cruciate ligament and the TPLO surgical technique as a solution, in order to contribute to advances in the field of orthopedics. The information was obtained through follow-up and review of the patient's medical record, photographic record of the exams for which the patient was submitted, and literature review in articles on the Scielo and Google Academic platforms.